Effect of Organic Fertilizer Products on the Growth and Health of Acacia Crassicarpa Seedlings - Syaffiary, Syaffiary; Antonius, Sarjiya; Said, Dahlan; Nugraha, Agus Kurnia; Gafur, Abdul (KnE Life Sciences, 2022)
Acacia crassicarpa seedlings face challenges with growth and health. Xanthomonas leaf blight, Fusarium wilt, and leaf spots caused by Pestalotiopsis or Phaeotrichoconis are all major nursery diseases of A. crassicarpa. This study was carried out to consider solutions for improving seedling conditions. The growth and health of A. crassicarpa seedlings were assessed using two commercial products: an organic biofertilizer (LOB-BS) and an organic multipurpose fertilizer (OMF). The LOB-BS + basal fertilizer (BF) treatment led to a higher germination rate than the other treatments, according to our findings. Similarly, at 12 weeks after sowing, the same treatment produced the tallest A. crassicarpa seedlings. In comparison to other treatments, the incidence of Xanthomonas leaf blight, Fusarium wilt, and leaf spot diseases was lower in the plots of OMF and OMF + BF treatments. Based on these findings, the LOB-BS product could be used to improve the growth of A. crassicarpa seedlings, while the MOF product could be used to reduce the incidence of major A. crassicarpa seedling diseases in the nursery. Keywords: Fusarium, leaf spot, Xanthomonas, organic biofertilizer (LOB-BS), organic multipurpose fertilizer (OMF).